Contraception and folates: new opportunities for prevention and treatment - V N Prilepskaia; E G Nazarenko (IP Berlin A.V., 2018)
The article presents the latest information on new contraceptive drugs containing folic acid in the form of levomefolate calcium, which have not only contraceptive properties, but also have new capabilities for preparing for a future pregnancy and preventing neural tube defects in the fetus, as well as treating cosmetic defects such as mild and moderate acne vulgaris, depressive disorders, fluid retention in the body.